Polymorphisms of Dopamine Receptor Genes and Risk of L-Dopa–Induced Dyskinesia in Parkinson’s Disease - Cristoforo Comi (International Journal of Molecular Sciences, 2017)
L-dopa–induced dyskinesia (LID) is a frequent motor complication of Parkinson’s disease (PD), associated with a negative prognosis. Previous studies showed an association between dopamine receptor (DR) gene (DR) variants and LID, the results of which have not been confirmed. The present study is aimed to determine whether genetic differences of DR are associated with LID in a small but well-characterized cohort of PD patients. To this end we enrolled 100 PD subjects, 50 with and 50 without LID, matched for age, gender, disease duration and dopaminergic medication in a case-control study. We conducted polymerase chain reaction for single nucleotide polymorphisms (SNP) in both D1-like (DRD1A48G; DRD1C62T and DRD5T798C) and D2-like DR (DRD2G2137A, DRD2C957T, DRD3G25A, DRD3G712C, DRD4C616G and DRD4nR VNTR 48bp) analyzed genomic DNA. Our results showed that PD patients carrying allele A at DRD3G3127A had an increased risk of LID (OR 4.9; 95% CI 1.7–13.9; p = 0.004). The present findings may provide valuable information for personalizing pharmacological therapy in PD patients.